2020
DOI: 10.1101/2020.01.13.904854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functionalized Mesoporous Silicas Direct Structural Polymorphism of Amyloid-β Fibrils

Abstract: The aggregation of Amyloid-b (Ab) is associated with the onset of Alzheimer's Disease (AD) and involves a complex kinetic pathway as monomers self-assemble into fibrils. A central feature of amyloid fibrils is the existence of multiple structural polymorphs, which complicates the development of disease-relevant structure-function relationships. Developing these relationships requires new methods to control fibril structure. In this work, we demonstrate that mesoporous silicas (SBA-15) functionalized with hydro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…As reported previously 22 and as seen in Figure 2b (generation 0), WT Aβ 1−40 primarily formed fibrils with crossover distances of 120 nm (73 ± 14%), 60 nm (7 ± 7%), and no crossovers (20 ± 9%). 26 In order to evaluate if any fibril polymorphs were able to pass on their structure, we seeded 30 μM of fresh WT Aβ 1−40 monomer with 5 μM of pre-formed fibril "seeds." We repeated this process twice to produce three generations of fibrils.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously 22 and as seen in Figure 2b (generation 0), WT Aβ 1−40 primarily formed fibrils with crossover distances of 120 nm (73 ± 14%), 60 nm (7 ± 7%), and no crossovers (20 ± 9%). 26 In order to evaluate if any fibril polymorphs were able to pass on their structure, we seeded 30 μM of fresh WT Aβ 1−40 monomer with 5 μM of pre-formed fibril "seeds." We repeated this process twice to produce three generations of fibrils.…”
Section: ■ Resultsmentioning
confidence: 99%
“…23,24 While simulations measuring the nucleation barrier and the initial dimerization process in aggregate formation suggest kinetic control on fibril polymorphism, 25 our previous study using sodium dodecyl sulfate (SDS) to artificially accelerate amyloid aggregation to a rate similar to those of mesoporous silica materials demonstrated a nuance in kinetic control; similar kinetic lag times could still result in different fibril polymorph distributions depending on the nucleation condition. 26 As recent studies have shown that structural variants can display differing phenotypes and disease subtypes, 27−31 the large number of possible fibril conformations produced from different peptide sequences and nucleation in vitro and in vitro conditions complicates the development of effective therapeutics and hinders our understanding of the role of fibrils in disease progression.…”
Section: ■ Introductionmentioning
confidence: 99%